POST-VACCINATION IMMUNITY TO MEASLES IN CHILDREN WITH POST-COVID SYNDROME LITERATURE REVIEW (2ND PART) - Dilorom Toshtemirovna Kenzhaeva (Scholar Express Journals, 2025)
Measles is a highly contagious viral disease that has significantly decreased in prevalence over recent decades due to vaccination. However, in recent years, the situation with measles has worsened again in a number of countries, particularly in the context of the COVID-19 pandemic. The COVID19 pandemic and the associated restrictions have limited population-wide immunization coverage, which may affect the epidemiological situation of other infectious diseases, including measles. This article presents a review of several studies conducted by groups of scientists who monitored the health of children and analyzed their immune status related to measles vaccination following a coronavirus infection.
Keywords: measles; measles vaccine; preventive healthcare